Computational geometry, graphs and applications 9th international conference, CGGA 2010, Dalian, China, November 3-6, 2010, revised selected papers - Akiyama, Jin; Bo, Jiang; Kano, Mikio; Tan, Xuehou (Lecture notes in computer science, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the China-Japan Joint Conference on Computational Geometry, Graphs and Applications, CGGA 2010, held in Dalian, China, in November 2010. The 23 revised full papers presented were carefully selected during two rounds of reviewing and improvement from numerous submissions. All aspects of computational and discrete geometry, graph theory, graph algorithms, and their applications are covered.